2017
DOI: 10.1371/journal.pone.0188754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of merozoite invasion and transient de-sequestration by sevuparin in humans with Plasmodium falciparum malaria

Abstract: Severe malariaEven with the best available treatment, the mortality from severe Plasmodium falciparum malaria remains high. Typical features at death are high parasite loads and obstructed micro- vasculature. Infected erythrocytes (IE) containing mature parasites bind to the host receptor heparan sulfate, which is also an important receptor for merozoite invasion. To block merozoite invasion has not previously been proposed as an adjunctive therapeutic approach but it may preclude the early expansion of an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Since heparin treatment includes risks of causing potentially dangerous bleeding one might consider to use low-molecular heparin preparations with very low anticoagulant activity but preserved capacity to bind to HMGB1. One such heparinoid compound has been successfully tested clinically in phase I/II studies of Plasmodium falciparum malaria disease (Leitgeb et al 2017). This molecule also prevented neutrophil-induced lung plasma leakage in a murine sepsis model (Rasmuson et al 2019).…”
Section: Heparin and Heparinoid Compoundsmentioning
confidence: 99%
“…Since heparin treatment includes risks of causing potentially dangerous bleeding one might consider to use low-molecular heparin preparations with very low anticoagulant activity but preserved capacity to bind to HMGB1. One such heparinoid compound has been successfully tested clinically in phase I/II studies of Plasmodium falciparum malaria disease (Leitgeb et al 2017). This molecule also prevented neutrophil-induced lung plasma leakage in a murine sepsis model (Rasmuson et al 2019).…”
Section: Heparin and Heparinoid Compoundsmentioning
confidence: 99%
“…A nonanticoagulant LMW ROH, Sevuparin (Mw 7.4 kDa), obtained by mild acid hydrolysis of ROH, showed the same activity of UFH both in vitro and in vivo in severe malaria models [139]. Clinical trials are evaluating the adjuvant activity of Sevuparin both in malaria patients and subjects with sickle cell disease, an inherited form of anemia [140,141]. Another LMW ROH, Tafoxiparin (Mw 6.0 kDa) obtained by mild alkaline β-elimination, was found to disrupt rosettes, especially in the majority of fresh blood isolated from children with complicated malaria.…”
Section: Sevuparin (Df F01) and Tafoxiparin (Dfx232)mentioning
confidence: 99%
“…Methylene blue acts by inhibiting falciparum glutathione reductase and as a result, prevents haem polymerization [126]. Polysaccharide heparin analogue Sevuparin (DF02) which is taken as an adjunctive therapy retains the antiadhesive effects of heparin without the antithrombin properties and has been shown to block merozoite invasion, cytoadherence, and rosetting [198]. MMV39048 is an aminopyridine currently in Phase 2a (NCT02880241) trial, and its target was identified to be lipid phosphatidylinositol 4-kinase (PfPI4K).…”
Section: Drugs In the Pipelinementioning
confidence: 99%